Effect of Job Satisfaction on Work Discipline Mediated by Continuance Commitment - Dedi Hadian (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
This study aims to navigate the effect of job satisfaction on work discipline mediated by continuance commitment. Proving the research hypothesis uses a non-parametric approach. The data used are the results of a questionnaire given to employees at one of the Private Banks in the city of Bandung with a sample of 54 employees. The survey was conducted directly by visiting one of the Bank's offices in Badung City and randomly selected respondents who were willing to fill in the research questionnaire. The results of the study prove that there is an influence of job satisfaction on work discipline mediated by continuance commitment. The implications of the results of the study indicate that with a feeling of satisfaction with the work done will be able to improve the discipline of work that can be driven by continuance commitment owned by employees.